Chilaiditi syndrome: An unusual post-operative complication of congenital diaphragmatic hernia (Indian Journal of Case Reports, 2018)
Chilaiditi syndrome is a condition in which the hepatodiaphragmatic colonic interposition is accompanied by signs and symptoms such as pain abdomen, nausea, vomiting, and respiratory distress. Chilaiditi sign is defined as the asymptomatic radiological diagnosis of segmental interposition of a portion of large intestine or hollow viscera between the undersurface of liver and hemidiaphragm. The syndrome is managed conservatively. Recognition of this syndrome and its differentiation from pneumoperitoneum is important in patients with respiratory or gastrointestinal symptoms with a characteristic radiographic picture of this syndrome to prevent unnecessary surgical intervention. Right-sided congenital diaphragmatic hernias (CDHs) are rare in children and may mimic Chilaiditi syndrome. Here, we report the case of an 18-month-old girl, who was later on diagnosed as a case of Chilaiditi syndrome secondary to a post-operative repair of the right-sided CDH and was managed conservatively with the help of intravenous fluids and bronchodilators.